Organic xenobiotics removal in constructed wetlands, with emphasis on the importance of the support matrix - Dordio, Ana V. (2014)
Constructed wetlands (CWs) are increasingly popular as an efficient and economical alternative to conventional wastewater treatment processes for removal, among other pollutants, of organic xenobiotics. In CWs, pollutants are removed through the concerted action of their components, whose contribution can be maximized by careful selection of those components. Specifically for non-biodegradable organic pollutants, the materials used as support matrix of CWs can play a major role through sorption phenomena. In this review the role played by such materials in CWs is examined with special focus on the amount of research that has been conducted to date on their sorption properties relatively to organic compounds. Where available, the reports on the utilization of some of those materials on pilot or full-scale CWs are also recognized. Greatest interest has been directed to cheaper and widely available materials. Among these, clays are generally regarded as efficient sorbents, but materials originated from agricultural wastes have also gained recent popularity. Most available studies are lab-scale batch sorption experiments, whereas assays performed in full-scale CWs are still scarce. However, the available lab-scale data points to an interesting potential of many of these materials for experimentation as support matrix of CWs targeted for organic xenobiotics removal.